NOISE PROTECTION EQUIPMENT SYSTEM FOR CENTRIFUGING HELICOPTER SPAR TUBES - Yulia Anatolyevna Proskoryakova; Petr Danilovich Motrenko (Advanced Engineering Research, 2013)
The experimental results of noise and vibration in the section of the centrifugal treatment of the helicopter longeron tubes are given. Noise sources determining very high level increase over limitary spectra are identified. As the noise reduction up to the sanitary norms in the source itself is impossible, observing the sanitary standards is possible only through calculating and designing a soundproof construction with the required acoustic protection value. Thus, the noise protection system diagram presenting a safeguard with a high degree of pressurization is given at the end of the paper. The sanitary standards control is achieved as a result of the introduction of the package of measures including the noise enclosure for the facilities of the centrifugal treatment and the sound-absorbing revetment application on the shopfloor walls and the ceiling.